Happily ever afters - Bryant, Elise (Elise M.) (New York, NY : Balzer + Bray, an imprint of HarperCollinsPublishers, 2021)
"Sixteen-year-old Tessa Johnson has never felt like the protagonist in her own life. She's rarely seen herself reflected in the pages of the romance novels she loves. The only place she's a true leading lady is in her own writing, in the swoony love stories she shares only with Caroline, her best friend. When Tessa is accepted into the creative writing program of a prestigious art school, she's excited to finally let her stories shine. But when she goes to her first workshop, the words are gone. Fortunately, Caroline has a solution: Tessa just needs to find some inspiration in a real-life love story of her own. And she's ready with a list of romance novel-inspired steps to a happily ever after. Nico, the brooding artist who looks like he walked out of one of Tessa's stories, is cast as the perfect Prince Charming. . . She's well on her way to having her own real-life love story, but is it the one she wants, after all?"--Provided by publisher.
School Library Journal starred, November 2020
Booklist, November 2020
Library Media Connection, November 2020
Publishers Weekly Annex, January 2021
Young Adult
Keywords: Teenage girls -- Juvenile fiction; Authorship -- Technique -- Juvenile fiction; Romance fiction -- Juvenile fiction; Man-woman relationships -- Juvenile fiction; Teenage girls -- Fiction; Authorship -- Technique -- Fiction; Romance fiction -- Fiction; Man-woman relationships -- Fiction; Romance fiction